Regarding the article “Irrational fixed dose combinations in Nepal: Need for intervention” (KUMJ, Vol 6, No. 3, Issue 23, p. 399-405) - Poudel, A; Khanal, S; Alam, K; Palaian, S (Kathmandu University Medical Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> doi: 10.3126/kumj.v6i4.1753 Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 537-538